Incongruent Voting or Symbolic Representation? Asymmetrical Representation in Congress, 2008–2014. Issue 3 (21st September 2022) - Cayton, Adam; Dawkins, Ryan
Abstract : The electoral connection incentivizes representatives to take positions that please most of their constituents. However, on votes for which we have data, lawmakers vote against majority opinion in their district on one out of every three high-profile roll calls in the U.S. House. This rate of "incongruent voting" is much higher for Republican lawmakers, but they do not appear to be punished for it at higher rates than Democrats on Election Day. Why? Research in political psychology shows that citizens hold both policy-specific and identity-based symbolic preferences, that these preferences are weakly correlated, and that incongruous symbolic identity and policy preferences are more common among Republican voters than Democrats. While previous work on representation has treated this fact as a nuisance, we argue that it reflects two real dimensions of political ideology that voters use to evaluate lawmakers. Using four years of CCES data, district-level measures of opinion, and the roll-call record, we find that both dimensions of ideology matter for how lawmakers cast roll calls, and that the operational-symbolic disconnect in public opinion leads to different kinds of representation for each party.